Kolonijalizam u socijalističkom diskursu (1948. – 1953.) - Blažetin, Vjekoslav (SlavVaria, 2022)
Colonialism in socialist discourse (1948–1953). This work is concerned with the relations between colonialism and socialism in the period between 1948 and 1953. The research presupposes that socialism is a labeling term with connotations that help create its own sense of reality through which it also de-termines the direction of such a relationship. Through discourse analysis, this work points out logical paradoxes apparent in the represented relations using a corpus of newspaper articles (from Hungary, the Soviet Union and Yugoslavia) and cartoons (published in the satirical magazines Ludas Matyi and Kerempuh) as its basis. On the one hand the work concludes that the anti-Titoistic dis-course utilizes colonialism to paint Tito as an agent of imperialism and a help-ing hand to the colonizers, while on the other it determines that the pro-Titoistic discourse represents the „Informbiro periodˮ states as colonies of the Soviet Union and at the same time the Soviet Union itself is being presented in the role of the „Eastern exploiter.ˮ